A novel puromycin decorporation method to quantify skeletal muscle protein breakdown: a proof-of-concept study - Crossland, Hannah; Smith, Kenneth; Atherton, Philip J.; Wilkinson, Daniel J. (Elsevier, 2017)
The precise roles that the major proteolytic pathways play in the regulation of skeletal muscle mass remain incompletely understood, in part due to technical limitations associated with current techniques used to quantify muscle protein breakdown (MPB). We aimed to develop a method to assess MPB in cells, based on loss of puromycin labelling of translated polypeptide chains. Following an initial 24 h incubation period with puromycin (1 μM), loss of puromycin labelling from murine C2C12 myotubes was assessed over 48 h, both in the presence or absence of protein synthesis inhibitor cycloheximide (CHX). To validate the method, loss of puromycin labelling was determined from cells treated with selected compounds known to influence MPB (e.g. serum starvation, Dexamethasone (Dex), tumour necrosis factor alpha (TNF-α) and MG-132)). Reported established (static) markers of MPB were measured following each treatment. Loss of puromycin labelling from cells pre-incubated with puromycin was evident over a 48 h period, both with and without CHX. Treatment with Dex (−14 ± 2% vs. Ctl; P < 0.01), TNF-α (−20 ± 4% vs. Ctl; P < 0.001) and serum starvation (−14 ± 4% vs. Ctl; P < 0.01) caused a greater loss of puromycin labelling than untreated controls, while the proteasome inhibitor MG-132 caused a relatively lower loss of puromycin labelling (+15 ± 8% vs. Ctl; P < 0.05). Thus, we have developed a novel decorporation method for measuring global changes in MPB, validated in vitro using an established muscle cell line. It is anticipated this non isotopic-tracer alternative to measuring MPB will facilitate insight into the mechanisms that regulate muscle mass/MPB both in vitro, and perhaps, in vivo.